Community-Based Child Protection Organizing Design in Cianjur - Nisa, Nuriyatuddin Khoyrun; Yuliani, Dwi; Susilawati (GoAcademica Research & Publishing, 2025)
Community-based child protection in Limbangansari Village was initially weak. The implementation of the Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM) programme in this location was not yet optimal, lacked organization, and resource management was insufficient to support the adequacy and sustainability of activities. Based on these issues, this study aims to develop a community-based child protection organizational model in Limbangansari Village, Cianjur District, Cianjur Regency. The study employs a qualitative approach using the Participatory Action Research (PAR) method. Data collection techniques include in-depth interviews and Focused Group Discussions (FGD) involving local stakeholders, document analysis, and observation. The research results show that the development of the model has successfully improved the organization of child protection, as evidenced by improvements in structure, clearer task distribution and child protection mechanisms, broader networks, and enhanced human resource capacity development management, thereby increasing activities. This development has succeeded in raising public awareness of child protection, increasing active community participation in activities, and enabling a faster response to child cases.